Scenario Planning Analysis of Companies That Help Save Other Companies Experiencing Financial Distress - Bagas Azhar Pratama; Willem A. Makaliwe (Eduvest - Journal of Universal Studies, 2025)
This study aims to develop strategic scenarios through in-depth interviews using thematic analysis as the foundation for formulating rescue measures for a company experiencing financial distress, specifically the integration of PT B (Persero) Tbk into PT A (Persero). The analysis produced 11 combined scenarios, categorized into three outlooks—pessimistic, moderate, and optimistic—each forming the basis for financial and key ratio projections. These projections are subsequently used to conduct a company valuation employing the Scenario Discounted Cash Flow (SDCF) approach, encompassing both levered and unlevered methods through Discounted Cash Flow (DCF) and constant growth valuation models. The primary differences among the scenarios are reflected in fundamental factors such as integration continuity, market optimism, cost efficiency, and restructuring success. These factors directly impact the company’s profitability, solvency, and liquidity. The findings reveal that the optimistic scenario indicates a successful integration and comprehensive financial recovery; the moderate scenario shows limited improvement with ongoing risks; and the pessimistic scenario underscores a standalone operation of PT A. Practically, the study offers strategic insights for policymakers in designing restructuring policies, risk mitigation plans, and business continuity strategies. In terms of originality, this research makes a significant contribution by integrating scenario planning, financial ratio analysis, and SDCF-based valuation to assess distressed company valuation, an approach rarely applied in academic studies related to Indonesia’s construction sector.